Microstructure and Mechanical Property of Al6Si2Cu Alloy Subjected to Double-Solution Heat Treatment - Seongbin An; Minsuk Kim; Chaeeul Huh; Chungseok Kim (Metals, 2021)
This study aims to develop the mechanical properties of the Al6Si2Cu aluminum alloy through the double-solution treatment. In addition to the Al matrix, large amounts of coarse eutectic Si, Al2Cu intermetallic, and Fe-rich phases were generated through thermo-calc simulation in agreement with the equilibrium phases. The eutectic Si phase is fragmented and spheroidized by the solution treatment as the heat treatment temperature and time increase. The Al2Cu intermetallic phase is dissolved into the Al matrix, resulting in an increase in both strength and elongation. The second-step solution temperature at 525 °C should be an optimum condition for enhancing the mechanical properties of the Al6Si2Cu aluminum alloy.